Farm mechanization – trends and policy for its promotion in India - TIWARI, P S; SINGH, K K; SAHNI, R K; KUMAR, V (The Indian Journal of Agricultural Sciences, 2019)
Indian agriculture is diverse and capable of producing most of the food and horticultural crops of the world. In spite of its top ranking in production of a number of crops including rice, wheat, sugarcane, fruits and vegetables, the stagnancy in productivity and shortage of agricultural produce are two major bottlenecks of Indian agriculture. Several studies suggest a direct correlation between farm mechanization and crop productivity. It saves inputs like seeds and fertilizers by 15-20%, labour requirement and operational time by 20-30%, increases cropping intensity by 5-20% and crop productivity by 10-15%. At present, Indian farmers are adopting farm mechanization at a faster rate in comparison to recent past. Farm power availability from tractors has grown from 0.007 kW/ha in 1960-61 to 1.03 kW/ha in 2013-14 and it is further estimated to reach 3.74 kW/ha by 2032-33. According to the World Bank estimates, half of the total Indian population would be in urban areas by 2050. It is further estimated that the percentage of farm workers of total work force would reduce to 49.9% in 2033 and 25.7% in 2050 from 54.6% in 2011. The share of agricultural workers in total power availability in 1960-61 was about 16.3%, which is going to reduce to 2.3% in 2032-33. The overall level of farm mechanization in the country is only 40-45% and 90% of the total farm power is contributed by mechanical and electrical power sources. To assure timeliness and quality in various field operations, the average farm power availability needs to be increased to a minimum of 2.5 kW/ha by 2020.